Trauma-Informed Healthcare Leadership? Evidence and opportunities from interviews with leaders during COVID-19 - Sonia Rose Harris; Alexis Amano; Marcy Winget; Kelley M Skeff; Cati G Brown-Johnson (BMC, 2024)
Abstract Background COVID-19 impacted the mental health of healthcare workers, who endured pressures as they provided care during a prolonged crisis. We aimed to explore whether and how a Trauma-Informed Care (TIC) approach was reflected in qualitative perspectives from healthcare leaders of their experience during COVID-19 (2020-2021). Methods Semi-structured interviews with healthcare leaders from four institutions were conducted. Data analysis consisted of four stages informed by interpretative phenomenological analysis: 1) deductive coding using TIC assumptions, 2) inductive thematic analysis of coded excerpts, 3) keyword-in-context coding of full transcripts for 6 TIC principles with integration into prior inductive themes, and 4) interpretation of themes through 6 TIC principles (safety; trustworthiness and transparency; peer support; collaboration and mutuality; empowerment, voice, and choice; and awareness of cultural, historical, and gender issues). Results The actions of leaders (n = 28) that were reported as successful and supportive responses to the COVID-19 pandemic or else missed opportunities reflected core principles of Trauma-Informed Care. To promote safety, leaders reported affirmative efforts to protect staff by providing appropriate physical protection, and enhanced psychological safety by providing channels for communication about emotional well-being. To promote trustworthiness and transparency, leaders listened to their staff, shared current COVID-19 information, and increased frequency of meetings to disseminate accurate information. To promote mutual support, strategies included wellness check-ins, sharing uplifting stories, affirming common goals, articulating fears, and leading by example. Examples of empowerment included: making time and adjusting modalities for flexible communication; naming challenges outside of the hospital; and functioning as a channel for complaints. Reported missed opportunities included needing more dedicated time and space for healthcare employees to process emotions, failures in leadership managing their own anxiety, and needing better support for middle managers. Awareness of the TIC principle of cultural, historical, and gender issues was largely absent. Results informed the nascent Trauma-Informed Healthcare Leadership (TIHL) framework. Conclusions We propose the Trauma-Informed Healthcare Leadership framework as a useful schema for action and analysis. This approach yields recommendations for healthcare leaders including creating designated spaces for emotional processing, and establishing consistent check-ins that reference personal and professional well-being.